Inovasi Pembuangan Limbah Domba Otomatis Sederhana di Ratu Domba Indonesia, Desa Tamansari, Kec. Wuluhan, Kabupaten Jember - Rizal, Rizal (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This community-based research aims to implement and evaluate a simple automatic sheep waste disposal system at Ratu Domba Indonesia, Tamansari Village, Wuluhan District, Jember Regency. The program was carried out starting on June 1, 2025, using a sheepfold measuring 4 meters in length and 1.5 meters in width, housing seven crossbred sheep aged five to six months. The implementation method included direct installation, resource management, and periodic evaluation to assess cleanliness, efficiency, and ease of waste handling. The results indicate that the installation effectively maintained a dry and clean condition beneath the sheepfold throughout all evaluation stages. Minor technical adjustments, such as adding wire supports to prevent solid waste spillage, were required during the implementation period but did not reduce the system’s overall performance. Farmers reported reduced cleaning time and improved convenience in managing both feces and urine. The findings demonstrate that a simple and low-cost technological innovation can significantly improve sanitation and operational efficiency in small-scale sheep farming. This innovation has the potential to be replicated and further developed to support sustainable livestock waste management in rural farming systems.